Facile synthesis of CaFe 2 O 4 for visible light driven treatment of polluting palm oil mill effluent: Photokinetic and scavenging study - Charles, A. (2019)
In this paper, a facile synthesis method for CaFe 2 O 4 is introduced that produces a catalyst capable of significant photocatalytic degradation of POME under visible light irradiation. The co-precipitation method was used to produce two catalysts at calcination temperatures of 550 °C and 700 °C dubbed CP550 and CP700. CP550 demonstrated the maximum COD removal of 69.0 at 0.75 g/L catalyst loading after 8 h of visible light irradiation which dropped to 61.0 after three consecutive cycles. SEM images indicated that the higher calcination temperature of CP700 led to annealing which reduced the pore volume (0.025 cm 3 /g) and pore diameter (10.3 nm) while simultaneously creating a smoother and more spherical surface with lower S BET (9.73 m 2 /g). In comparison, CP550 had a rough hair-like surface with higher S BET (27.28 m 2 /g) and pore volume (0.077 cm 3 /g) as evidenced by BET analysis. XRD data indicated the presence of CaFe 5 O 7 in the CP550 composition which was not present in CP700. The presence of Wustite-like FeO structures in CaFe 5 O 7 are likely the cause for lower photoluminescence intensity profile and hence better charge separation of CP550 as these structures in CaFe 2 O 4 have been known to increase resistivity and electron localization. The COD removal of CP550 dropped from 69.0 to just 7.0 upon adding a small quantity of isopropanol into the reaction mixture indicating hydroxyl radicals as the primary reactive oxidative species. © 2019 Elsevier B.V.